Kedudukan Notaris dalam Penyimpanan Sertipikat pada Masa Pelaksanaan Perjanjian Pengikatan Jual Beli di Kota Padang - Irma Aisyah; Busyra Azheri; Muhammad Hasbi (UNES Law Review, 2023)
One of the authorities of a notary is in the making of a Sales and Purchase Agreement (SPA), which is a preliminary agreement between the seller and the buyer before the official sale and purchase deed is made in front of a Land Deed Official. Because there are requirements that have not been fulfilled, in accordance with the principles of real, cash, and clear sale and purchase, the Notary has the independence to keep the certificate for the safety of the parties who want or require the Notary to hold (store) the certificate. The Notary takes this action because of concerns that may arise if the certificate is held by the seller or buyer, and the Notary usually takes this precaution until the payment is made. With this, there is a legal vacuum where the Notary takes action to keep the certificate to avoid potential risks, but there are no regulations that protect the Notary from all the risks. The issue addressed in this paper is : how is the legal position of a Notary if it is linked to the storage of the certificate during the implementation of the Sales and Purchase Agreement in Padang City and what if one side of the party takes the certificate stored by the Notary without the presence of all members of the party of the agreement. In this research, the method used is juridical empirical, which is an approach to the problem through legal research by looking at the applicable legal regulations and will produce theories about the existence and function of law in society. According to the result of this research it is found that: 1) The storage of land certificates in the Sale and Purchase Agreement (SPA) is outside the Notary's authority and obligation based on Law Number 2 of 2014 concerning Notary Position. The Notary's action in receiving the storage of land certificates as a neutral stance towards the parties to ensure legal certainty and protection. 2) In practice, the Notary will not provide the certificate to one party if the other party is not present. This is to prevent losses to the other party and in accordance with Article 16 paragraph (1) letter (a) of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Position (hereinafter referred to as UUJN), in carrying out their duties, the Notary is obliged to act with trustworthiness, honesty, impartiality, independence, and to protect the interests of the parties involved in the legal act.